Experimental and Numerical Study on the Blast Performance of RC Shear Walls Under Uniaxial Compression - Wenzhe Luo; Rongyue Zheng; Wei Wang; Chenzhen Ye (Buildings)
This study addresses a critical gap in blast-resistant design by investigating the influence of axial compression ratio—a previously underexplored parameter—on the dynamic response of reinforced concrete (RC) shear walls under close-in explosions. While existing research has focused on conventional loading scenarios, the interplay between axial compression and blast effects remains poorly understood, despite its practical significance for structural safety in high-risk environments. Through a combined experimental and numerical approach, three half-scale RC shear walls were tested under blast loading, complemented by simulations analyzing key parameters (aspect ratio, axial compression ratio, boundary conditions, and charge weight). The results demonstrate that a moderate axial compression ratio (around 0.3) enhances structural stiffness and reduces displacement, effectively helping to control wall damage. Boundary conditions were also found to affect failure modes: walls with stiffer end restraints exhibited reduced deformation but more brittle cracking. Lower aspect ratios (i.e., wider walls) improved blast resistance, and peak displacement progressively increased with the charge weight. These findings provide actionable insights for optimizing RC shear wall design in blast-prone infrastructures, balancing ductility and load capacity. By linking theoretical analysis to practical design criteria, this study advances blast-resistant engineering solutions.